Analysis of HLA-D region-associated molecules with monoclonal antibody. - Charron, D J (1979)
A group of monoclonal antibodies directed against nonpolymorphic HLA-D antigens (human Ia antigens) was produced by somatic cell hybridization. One of these antibodies was used to analyze the two-dimensional polyacrylamide gel electrophoretic pattern of the HLA-D alloantigens from different HLA-D homozygous B-cell lines. Two-dimensional gels of [35S]methionine-labeled cell extracts immunoprecipitated by a monoclonal antibody directed against HLA-D antigens showed a complex set of spots whose electrophoretic pattern varied according to the HLA-D type. The major HLA-D-related electrophoretic polymorphism was found in the basic and smaller (26,000-28,000 daltons) HLA-D polypeptides. These patterns represent allele-specific "fingerprints" of different HLA-D genotypes. There are striking similarities with respect to number, size, and charge spectrum among HLA-D polypeptides and the murine I-A and I-E subregion polypeptides, suggesting a similar genetic organization and molecular complexity in both species.